Increased level of malondialdehyde in preterm labor - Yesi Mustika Sari; Eti Yerizel (Acta Biochimica Indonesiana, 2021)
Background: The pathophysiological mechanism associated with spontaneous preterm delivery is oxidative stress through the increased formation of reactive oxygen species (ROS) due to lipid peroxidation. Malondialdehyde (MDA) is one of the biomarkers of oxidative stress produced through the lipid peroxidation process. Objective: The aim of this study is to observe the difference in MDA levels among preterm labor compared to full-term labor. Methods: Observational research was conducted with a comparative cross-sectional design. Maternal venous blood samples were taken from private hospitals and midwives in Padang city and Aro Suka Hospital Solok Regency. Samples were selected by consecutive sampling and divided into two groups with a total of 40 samples. MDA level was measured using the spectrophotometry method. Results: MDA levels in preterm delivery were 3,6±0.42 nmol/mL and in full-term delivery were 2.9±0.33 nmol/mL. Conclusion: There was a significant difference in MDA levels between preterm labor and full-term delivery. MDA levels in preterm childbirth were higher than MDA levels in full-term delivery.